MENINGKATKAN PEMAHAMAN PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG MENGGUNAKAN MEDIA KONKRIT DI KELAS V SDN 186/1 SRIDADI - Arabi, M. Akram; Aisah, Nur; Nurhalizah, Siti; Dwi Angraini, Rima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics is a study material that has an abstract object and is built through a deductive reasoning process, that is, the truth of a concept is obtained as a logical result of the previous truth so that the relationship between concepts in mathematics is very strong and clear. Thus, it can be interpreted that abstract mathematical objects are not easily observed by the five senses. So that it may be difficult for some students to understand the mathematics material delivered by the teacher. To facilitate the understanding of abstract mathematical objects, an intermediary that is concrete or observable by the five senses is needed to reduce the abstraction. The mathematical object that is a real object is called a mathematics learning aid. Therefore, the researcher utilizes learning media by using teaching aids in building space materials for elementary school education. The subject of this study is a student of class V of SDN 186/I Sridadi. The data collection techniques used are, observation, interviews, tests, and documentation. The results obtained from the use of learning media in the form of classroom building props, students achieved completeness of 72.2%, incomplete students by 27.2%, and an increase in student learning outcomes by 53.9%. With this, the use of learning media in the form of mathematics teaching aids for class V students is effective to be used in the learning process. Keywords: building space, concrete media, mathematics